2020
DOI: 10.3390/ijms21041407
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression Effect of SLC7A5/SLC3A2 to Predict Response to Endocrine Therapy in Oestrogen-Receptor-Positive Breast Cancer

Abstract: The majority of breast cancers are oestrogen-receptor-positive (ER+) and are subject to endocrine therapy; however, an unpredictable subgroup of patients will develop resistance to endocrine therapy. The SLC7A5/SLC3A2 complex is a major route for the transport of large neutral essential amino acids through the plasma membrane. Alterations in the expression and function of those amino-acid transporters lead to metabolic reprogramming, which contributes to the tumorigenesis and drug resistance. This study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Additionally, the amino acid transporter SLC7A5 was also among the upregulated DEGs in the unresponsive cases identified in this study. In support of this finding, we have previously along with others reported that SLC7A5 high expression correlates with poor clinical outcome and poor response to endocrine therapy in patients with luminal breast cancer [9][10][11]. Altogether, the above findings indicate a good reliability of the analysis performed in identifying the DEGs that are associated with prognosis in luminal breast cancer and sensitivity to endocrine treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, the amino acid transporter SLC7A5 was also among the upregulated DEGs in the unresponsive cases identified in this study. In support of this finding, we have previously along with others reported that SLC7A5 high expression correlates with poor clinical outcome and poor response to endocrine therapy in patients with luminal breast cancer [9][10][11]. Altogether, the above findings indicate a good reliability of the analysis performed in identifying the DEGs that are associated with prognosis in luminal breast cancer and sensitivity to endocrine treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Three hub genes, SLC7A5, MYLIP, and DLX5 were overlapped between module green and DEGs of Ad4h. SLC7A5 (also known as LAT1), a sodium-independent Neutral Amino Acid transporter, has been widely investigated in various cancer cells [ 35 ]. Recently, Beaumatin et al, demonstrated that SLC7A5 could affect cellular growth, metabolic homeostasis, and differentiation by activating mTORC1 through DRAM-1, which was a key regulator for controlling adipocyte signalling and differentiation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ca 2+ channels MCOLN1, TPCN1, and TPCN2, for example, were expressed at very similar levels in all cell lines, while the amino acid and oligopeptide transporting members of the solute carrier (SLC) family showed both similar and highly variable expression patterns. SLC3A2 and SLC7A5, which are known to heterodimerize (Alfarsi et al, 2020), exhibited the highest dynamic range of all proteins in this group with differences of up to 135-fold between the highest (HeLa) and lowest (NIH3T3) expressing cell line, respectively. On the other hand, the sodium dependent amino acid transporter SLC38A7, which was shown to be essential for the extracellular protein dependent growth of cancer cells (Verdon et al, 2017), was with a dynamic range of protein expression of ~2-fold most stable.…”
Section: Cell Line Specific Differential Expression Of Lysosomal Protmentioning
confidence: 96%